Cover Feature: A Review on Recent Developments and Prospects for the Oxygen Reduction Reaction on Hollow Pt‐alloy Nanoparticles (ChemPhysChem 13/2018). Issue 13 (20th June 2018) - Asset, Tristan; Chattot, Raphaël; Fontana, Marie; Mercier‐Guyon, Benjamin; Job, Nathalie; Dubau, Laetitia; Maillard, Frédéric
Abstract : The Cover Feature shows an artist's view of the highly defective structure of hollow Pt‐alloy nanoparticles. The Review addresses the mechanisms of formation and growth of these peculiar nanocatalysts, and show how distortion of the lattice parameter, polycrystallinity and pores combine to enhance the kinetics both for the oxygen electroreduction reaction and for electrooxidation reactions. More information can be found in the Review by T. Asset et al. onpage 1552 in Issue 13, 2018 (DOI:10.1002/cphc.201800153 ).